Fungal Succession and Decomposition of Acacia mangium Leaf Litters in Health and Ganoderma Attacked Standings - SAMINGAN SAMINGAN; LISDAR IDWAN SUDIRMAN (HAYATI Journal of Biosciences, 2009)
Leaf litters of Acacia mangium play an important functional role in ecosystem, producing sources of nutrients and giving diversity of microorganisms. Understanding the variation in fungal populations in A. mangium forest is important due to the roles of fungi in regulating populations of other organisms and ecosystem processes. For these purposes, the tests were conducted under two years old of health standing (2S) and Ganoderma attacked standing (2G) using litterbag method. Litter weight loss and lignin, cellulose, C, N contents were measured each month during eight months of decomposition, as well as fungal community involved was observed. Litter weight loss and lignin, cellulose, C, N contents were measured each month during eight months of decomposition, as well as fungal community involved was observed. After eight months of decomposition, litter weight losses were low up to 34.61% (k = 0.7/year) in 2S and 30.64% (k = 0.51/ year) in 2G, as well as lignin weight losses were low up to 20.05% in 2S and 13.87% in 2G. However, cellulose weight losses were 16.34% in 2S and 14.71% in 2G. In both standings, the numbers of fungal species were 21 and 20 respectively, while the total of fungal populations tends to increase after one month of decomposition and tend to decrease in the last three months. In the first and second months of decomposition fungal species were dominated by genera of Penicillium and Aspergillus and the last three months by Trichoderma, Phialophora, and Pythium. Key words: fungal succession, decomposition, leaf litters, A. mangium